Coupled Hydraulic and Electronic Regulation for Banki Turbines. (2016) - Sammartano, Vincenzo; Filianoti, Pasquale; Sinagra, Marco; Tucciarelli, Tullio; Scelba, Giacomo; Morreale, Gabriele
Abstract: The potential benefit of coupling hydraulic and electronic regulation to maximize the energy production of a Bank turbine in hydraulic plants is analyzed and computed with reference to a specific case. Design criteria of the Banki turbine inside hydraulic plants are first summarized, along with the use of hydraulic regulation in the case of constant water head and variable discharge at the end of aqueducts feeding water distribution systems. Optimal turbine impeller rotational speed is derived and traditional, as well as innovative systems for electricity production according to controlled rotational speed of the generator are presented. The study case at the purification plant named Risalaimi, in Italy, is analyzed, and the potential production of energy along the year is computed according to the known monthly average demand and two possible choices: the choice of hydraulic regulation only, called CFT1, and the choice of coupled hydraulic and electric regulations, called CFT2. The Return time of Capital Investment (RCI) is then computed for both the CFT1 and CFT2 cases. The result is that the CFT2 choice provides an increment of the total produced energy, along with an increment of about 30% of the corresponding RCI.